(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1867)
The author discusses the importance of the carved oak ceiling in the Audience Chamber of Holyrood Palace in terms of its significance to both art and heraldry. The article concludes with a description of the heraldic shields on the Holyrood ceiling and an attempt to date when the ceiling was carved.